Produksi Biodiesel Dari Minyak Nyamplung Dengan Katalis Ni/Lempung - Taufik Kharnofa; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The research has been done to produce biodiesel from calophyllum inophyllum oil with Ni/clay catalyst. Several variations of the process variables were done to assess its influence on acquisition (yield) of biodiesel and quality of biodiesel produced. The variables are used consist of a dependent variable and independent variable. Dependent variables are calophyllum inophyllum oil weight 50 grams, the catalyst concentration Ni / clay 0.5%-b oil, reaction temperature of 60 °C and a reaction time of 90 minutes, while the independent variable which variation mole ratio of oil : methanol 1: 6, 1: 9 and variations of Ni metal impregnation 0% -w (no metal) 1%-w, 2%-w and 3%-w samples of clay. This research has given result the highest yield of 95.36% biodiesel obtained in the use of Ni(3%)/clay catalyst and the mole ratio of oil : methanol of 1: 9. The biodiesel produced has a density of 883 kg/m3, kinematic viscosity of 4,46 mm2/s, acid number of 0.50 mg KOH / g sample and the flash point of 155°C respectively.Keywords: Biodiesel, Ni/Clay Catalyst, Calophyllum Inophyllum Oil